2019
DOI: 10.1007/s10562-019-03034-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Iron-Molybdate Catalysts for Selective Oxidation of Methanol to Formaldehyde: Influence of Preparation Method

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…This phenomenon is quite usual in commercial MoO 3 -containing catalysts, such as the ferric-molybdatebased catalyst for methanol selective oxidation to formaldehyde. 52 In the case of spent Mo5S, FE-SEM data (Fig. 13) confirm the presence of Mo-rich particles, well visible in BSE micrograph, even though their dimensions are far smaller and they had partially lost the evidenced acicular form of the fresh material showing a more rounded shape in the exhaust material.…”
Section: Catalytic Activity In Ethanol Conversion In the Presence Of Oxygensteady-state Experimentsmentioning
confidence: 58%
“…This phenomenon is quite usual in commercial MoO 3 -containing catalysts, such as the ferric-molybdatebased catalyst for methanol selective oxidation to formaldehyde. 52 In the case of spent Mo5S, FE-SEM data (Fig. 13) confirm the presence of Mo-rich particles, well visible in BSE micrograph, even though their dimensions are far smaller and they had partially lost the evidenced acicular form of the fresh material showing a more rounded shape in the exhaust material.…”
Section: Catalytic Activity In Ethanol Conversion In the Presence Of Oxygensteady-state Experimentsmentioning
confidence: 58%
“…The findings of Ivanov and Dimitrov [82] and Andersson [20] were also substantiated in the studies by Raun et al [43,87,88] utilizing Raman spectroscopy, XRD, XPS, SEM, and STEM on powder samples used at 384-416 • C for up to 600 h on stream. Excess MoO 3 evaporated (within 10 h), then Fe 2 (MoO 4 ) 3 was reduced to the Mo depleted phases FeMoO 4 (10-250 h on stream) and Fe 2 O 3 (observed after 600 h on stream) due to the loss of Mo during operation.…”
Section: Deactivationmentioning
confidence: 59%
“…It is necessary for the oxygen vacancy to be reoxidized in time for the activity and selectivity to remain constant in the long term. Raun [31] also found that the Mo structure could influence the stability of Mo-Fe catalysts. A lower rate of catalyst deactivation was observed for the large h-MoO 3 compared with α-MoO 3 .…”
Section: Temperature (℃)mentioning
confidence: 99%